1998
DOI: 10.1086/314454
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Responses toMycobacterium tuberculosisAntigens by Human Alveolar Lymphocytes during Active Pulmonary Tuberculosis

Abstract: Responses to mycobacterial and nonmycobacterial antigens were examined in bronchoalveolar cells (BAC) and peripheral blood mononuclear cells (PBMC) from patients with active pulmonary tuberculosis (n=16) and healthy subjects (n=23). DNA synthesis in BAC (but not PBMC) from tuberculosis patients was significantly increased in response to the mycobacterial antigens purified protein derivative (PPD), antigen 85, and mannose-capped lipoarabinomannan but not to nonmycobacterial antigens. The response to PPD was als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
79
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(94 citation statements)
references
References 54 publications
15
79
0
Order By: Relevance
“…Proportions of alveolar neutrophils were Յ1% in BAC of both HHC and CC. Median proportions of alveolar lymphocytes were 14.1 and 14.0% and of alveolar macrophages were 85.8 and 83.9%, in HHC and CC, respectively, similar to those in CC in previous studies (10,26).…”
Section: Characteristics Of Study Groups and Cellssupporting
confidence: 87%
See 2 more Smart Citations
“…Proportions of alveolar neutrophils were Յ1% in BAC of both HHC and CC. Median proportions of alveolar lymphocytes were 14.1 and 14.0% and of alveolar macrophages were 85.8 and 83.9%, in HHC and CC, respectively, similar to those in CC in previous studies (10,26).…”
Section: Characteristics Of Study Groups and Cellssupporting
confidence: 87%
“…A nonmycobacterial Ag prepared from Candida albicans (Candida; Greer Laboratories, Lenoir, NC) was used to assess the specificity of responses. All Ags were used in concentrations that resulted in peak stimulation, as determined in previous studies (10). Dose responses were determined for Ag 85A, Ag 85B, Ag 85C, ESAT-6, and ST-CF for optimal induction of DNA synthesis, and performance of IFN-␥ and IL-10 enzymelinked immunospot (ELISPOT) assays.…”
Section: Preparation Of Pbmcmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this relation was not always apparent in experimental conditions. Some investigators reported up regulation of this cytokine [22,25] and some showed the reverse [26,27]. In our earlier study with THP-1, we found a strain specific induction of IL-10.…”
Section: Discussionsupporting
confidence: 52%
“…Following penetration of the mucosal barrier, the bacteria are associated with intraepithelial leukocytes and subsequently conveyed to the draining lymph nodes (3). From human and animal models of tuberculosis infection, the primary effector cells implicated to date in the control of tuberculosis have been T lymphocytes and alveolar and interstitial macrophages (4). However, other cell types, such as dendritic cells (5), type II pneumocytes (6), endothelial cells, and fibroblasts (7), have been reported to phagocyte M. tuberculosis, suggesting that many other cell types may be involved in the immunological control of M. tuberculosis in the lung.…”
mentioning
confidence: 99%